The Growth of an Agribusiness Cluster in Catalonia: Evidence from the Olive Oil Industry - Ramon-Muñoz, Ramon (TSEG - The Low Countries Journal of Social and Economic History, 2016)
This article aims to contribute to an understanding of the evolution of agribusiness clusters. It focuses on Catalonia, one of Europe’s leading regions in the agro-food industry; and it takes as a case-study olive oil, a typical Mediterranean commodity. After identifying the cluster and the main stages of its evolution, the article shows that the three decades following the years around 1890 were the most dynamic period for the cluster. Whereas several factors contributed to the final outcome, this article suggests that the existence of previous processes of accumulation of skills, techniques, market and product knowledge and the capabilities of firms had a remarkable influence on the successful response of agents to developments and shocks from outside the cluster.